(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Flight data recorders (FDRs) represent one of the most critical elements of aircraft safety infrastructure, enabling post-incident investigation, operational analysis, and real-time condition monitoring. This article examines the historical development of flight data recording onboard devices, analyzes current technological trends, and evaluates prospective engineering solutions focused on improving data protection, survivability, and integration with intelligent aircraft systems. The paper also discusses transitions from mechanical and magnetic storage to solid-state and network-centric solutions, considering the emerging challenges of cybersecurity, electromagnetic interference, miniaturization, and autonomous data transmission.